TRADISI MANJAPUIK BALIMAU ANAK DARO PADA ACARA PERNIKAHAN DI KABUPATEN AGAM SUMATRA BARAT - Caca, Vitra Yuliza; Fasya, Teuku Kemal; Nasution, Abdullah Akhyar; Alawi, Muh. Fahrudin; Chalid, Ibrahim; Meliza, Richa (FISIP Universitas Malikussaleh, 2024)
This research examines the Manjapuik Balimau Anak Daro Tradition at Wedding Ceremonies (Levis-Strauss Structuralism Study, Nagari Pagadih, Palupuah District, Agam Regency, West Sumatra. The main focus in this research is to see and study how the origins of the Manjapuik Balimau Anak Daro Tradition occurred at weddings and government policies towards the Balimau manjapuik tradition. This research uses the Levis-Strauss Structuralism theory. In conducting this research, the data sources used in this research are primary and secondary data sources Data collection techniques used in this research are observation techniques, unstructured interviews, documentation and literature. Based on the results of this research, it can be found that the implementation of the balimau anak daro manjapuik tradition that occurs in Nagari Pagadih is a tribute to the prospective bride and groom who will hold the baralek event ( wedding reception) which was held at Bako's house. And to respect the traditions of their ancestors that have existed since ancient times. This Manjapuik Balimau tradition only applies to someone who wants to hold a baralek ceremony (wedding reception). The tradition of manjapuik balimau anak daro is considered good by the people of Nagari Pagadih, because by doing this they can preserve customs that have existed since ancient times.